Introduction: photography and twentieth-century German history - Umbach, Maiken; Harvey, Elizabeth (Cambridge University Press, 2015)
In the introduction to this special issue on photography and German history, we outline current research on using both professional and amateur or snapshot photography to elucidate problems in 20th-century German history. We argue that an approach is required that focuses on the transformative impact of the mass production and circulation of images in this period, and the way in which this altered people's consciousness of their own role vis-a-vis larger social and political process, and in changing the boundaries between public and private life. We also explore the role this practice played in enabling new forms of politics, including, but not confined to, so-called totalitarian regimes.